ANALISIS GAYA BAHASA PADA PUISI “KUBACA BISA” KARYA ABDUL WACHID - Dandi Permana; Mimin Sahmini; Rochmat Tri Sudrajat (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
This research is entitled Analysis of Poetry entitled “Kubaca Bisa” by Abdul Wachid. This research is a form of contribution to the scientific development of Indonesian Language and Literature in analyzing poetry. This study aims to describe and interpret the language style used in the poem entitled "Kubaca bisa" by Abdul Wachid. This research belongs to the type of qualitative descriptive research. Data collection techniques in this study using content analysis. The validity of the data in this study is centered on theory and uses interactive techniques, namely the data reduction stage, data presentation and conclusion drawing. Every poem has its own use of language. As the results of this study which show that the poem "Kubaca Bisa" contains metaphors, parallelism, rhetoric, hyperbole to alliteration. The style of language used in the poem aims to emphasize the meaning of the poem.